The Banking System of Bulgaria and the Processes of Redirection of Monetary Resources - Sotirova, Ekaterina (Research Papers, 2006)
In the study are examined the main problems of in the functions performed by the banking system in the economy and their development after beginning of 90’s. Two separated periods are defined – before and after introduction of currency board in the country. The aim of research is to pointed out to the efficiency of banking system in performing its role of funds redirection throw two periods, and bring to, if there is, the element of redistribution of wealth and incomes – as a result of financial intermediation.In the first period 1990-1997 a lot of elements of redistribution are observed. They are founded of the deformed way of performing mainly saving and credit functions. This restricted the transformation of savings into investments. After currency board the efficiency of banking rises. This creates the prerequisites for normal and effective financial intermediation. Bank system becomes one of the important factors of economic growth. With its development and functions the system helps to the processes of integration of Bulgarian economy to the European economic area.